Digitization and image-based structure-properties relationship evaluation of a porous gold micro-electrode. (August 2020) - Baux, A.; Couégnat, G.; Vignoles, G.L.; Lasseux, D.; Kuhn, A.; Carucci, C.; Mano, N.; Le, T.D.
Abstract: The advantage of using porous materials for biofuel cells and biosensors is their very large internal surface area (where electron exchange takes place) compared to the overall material volume, yielding much larger current densities than on a bare solid electrode of the same size. However, limitations occur because of mass transfer resistance through the pores. We describe here a bottom-up approach to optimize the design of such materials, through the analysis and modeling of their porous structure. Electrodes prepared by replicating stacked Langmuir-Blodgett films, with 1-μm diameter interconnected spherical pores, were studied. Since pore window dimensions are around 100 nm, Focused Ion Beam-Scanning Electron Microscopy (FIB-SEM) has been performed to obtain a 3D reconstruction of the porous medium. Then, a determination of the geometrical characteristics has been achieved through image analysis. The structure of the sphere packing, the shape and size of the connections between spheres, the distances between spheres, the sphere diameters and the specific surface area have been analyzed. The porous medium is close to a face-centered cubic arrangement of spherical pores, but several deviations from ideality are present: missing pores (point defects), stacking errors (dislocations), and incomplete connection between spheres (only 50% of the ideal sphere connections are present). The consequence of such defects on transport is studied through image-based simulations of mass diffusion in the actual porous medium and in similar ideal media. Graphical abstract: Unlabelled Image Highlights: Porous gold micro-electrodes were digitized in 3D and analyzed in detail. Focused Ion Beam/Scanning Electron Microscopy and image processing were used. The medium derives from a face-centered cubic packing of spheres, with defects. Defects are vacancies & dislocations; only half of the connections are effective. Defects have a relatively low impact on reactant diffusion.